In vivo-like 3-D model for sodium nitrite- and acrylamide-induced hepatotoxicity tests utilizing HepG2 cells entrapped in micro-hollow fibers. Issue 1 (December 2017) - Chu, Qiang; Zhao, Yiying; Shi, Xuer; Han, Wen; Zhang, Yanzhen; Zheng, Xiaodong; Zhu, Jing
Abstract To address the need for a high throughput toxicity test in the modern food industry, anin vivo -like 3-D cell model was constructed in this study to provide an alternative to controversial long-term animal models and to improve the sensitivity and accuracy of the traditional monolayer model. The model formed cell cylindroids within polyvinylidene fluoride (PVDF) hollow fibers and therefore mimicked the microenvironment of liver tissue. Microscopy methods were used, and liver-specific functions were measured to demonstrate the superiority of the model compared to the monolayer model, as well as to optimize the model for best cell performances. Later, toxicity tests of sodium nitrite and acrylamide were conducted in both the 3-D model and the monolayer model to study the sensitivity of the 3-D model in toxicity responses. As expected, HepG2 cells within the 3-D model responded at lower concentrations and shorter exposure times compared to cells within the monolayer model. Furthermore, western blot analysis of apoptosis pathways also supported the argument.